Patient Perception about Generic vs. Branded Medicines Prescribed in a Tertiary Care Hospital in Northern India -A Descriptive Study - Tripathi, Shailesh; Bhattacharya, Sudip (Indian Journal of Pharmacy Practice)
Background: The concept of generic prescription is widely accepted in various parts of the world. Nevertheless, it has failed to gain popularity in India due to factors such as non-availability and distrust on the product quality. However, since 2012, the Government of India, has initiated exclusive generic drug outlets called Jan Aushadhi stores. This study was undertaken to evaluate the experience and attitude of patients who were consuming generic drugs purchased from these stores. Materials and Methods: It was a questionnaire-based cross-sectional study where we have interviewed total 100 patients consuming generic and branded drugs, respectively. The perceived effectiveness, cost of therapy, quality of drugs was asked. Results: In our study 72 % participants heard about generic medicines and 65% knew the difference between generic and branded medicines. 67% agreed that generic medicines are cheaper than branded medicines but only 35% of them preferred to buy generic medicines. Most (64%) of the patients never asked his/her doctor or pharmacist (59%) to prescribe/ distribute generic medicines. Majority of them (61%) believed that generic medicines have lower quality than branded medicines. According to patients, 45% responded that doctors preferred branded medicines over generic medicines. In this hospital, 37% patients were prescribed generic medicines. Most of them (67%) did not become aware of the government rules about prescribing generic medicines. Only 24% responded that government should promote generic medicines. According to 13%of patients suggest that there should be more generic medicine shops present in the hospital. Interestingly, 45% of them suggested that generic medicines should be available in all medicine shops. Conclusion: Our findings suggest that knowledge and attitude about generic medicines among participants were poor. Some of them had wrong information, which is not a good sign for implementation and sustainability of Jan Aushadhi scheme in government hospitals.
Keywords: Branded drug; Cost of therapy; Generic prescription; Health policy.